2014
DOI: 10.1182/blood-2013-10-534313
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of dendritic cell development and fate determination of common myeloid progenitor by Mysm1

Abstract: Key Points Deletion of Mysm1 impairs development of steady-state DC, but no other myeloid lineages; monocyte, macrophage, and granulocyte. Mysm1 governs DC differentiation from CMP by regulating Flt3 expression via modulating histone modifications and mediating Pu.1 recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 41 publications
7
57
0
Order By: Relevance
“…controversial (23,56,59), we previously demonstrated its presence and function (15,20,44), and we confirmed its presence by real-time PCR in the present study in mouse liver tissue (data not shown). We acknowledge that several signaling pathways are likely to be involved in this phenomenon.…”
Section: Discussionsupporting
confidence: 94%
“…controversial (23,56,59), we previously demonstrated its presence and function (15,20,44), and we confirmed its presence by real-time PCR in the present study in mouse liver tissue (data not shown). We acknowledge that several signaling pathways are likely to be involved in this phenomenon.…”
Section: Discussionsupporting
confidence: 94%
“…S2 and S3). Because Mysm1 knockout does not affect the global ubH2A level, Mysm1 may control hematopoiesis (B-cell development, CLP fate determination, and natural killer cell maturation) by targeting a limited number of genes (23,24,39,40). Increased reactive oxygen species, γ-H2AX foci, and p53 level were observed in Mysm1 KO HSCs (23).…”
Section: Discussionmentioning
confidence: 99%
“…6 MYSM1 was also shown to regulate the differentiation of multiple hematopoietic lineages by activating Ebf1, Id2, or Flt3 transcription. 2,4,7 Nevertheless, the significance of p53 elevation in Mysm1 2/2 hematopoiesis has not been addressed. p53 is a central regulator of cellular stress responses.…”
Section: Introductionmentioning
confidence: 99%